Does the 3-aminobenzamide effect on bacterial translocation affect experimental acute necrotizing pancreatitis? - Sezai AYDIN,; A. Turan IŞIK,; Eşref ÇINAR,; Oktay DEMİR,; Cemal AKAY,; Mustafa ÖZYURT,; Salih DEVECİ,; M. Refik MAS, (Turkish Journal of Gastroenterology, 2019)
-